A Study of Superficial Sediments and Aquifers in Parts of Uyo Local Government Area, Akwa Ibom State, Southern Nigeria, Using Electrical Sounding Method. Issue 3 (2010) - Evans, U. F.; George, N. J.; Akpan, A. E.; Obot, I. B.; Ikot, A. N.
Abstract : Resistivity sounding method using Schlumberger electrodes configuration was employed to investigate the goe-eletrical properties of the subsurface in parts of Uyo Local Government Area of Akwa Ibom State, Nigeria. Within the maximum electrode spread, the area studied show sandy beds with five layers of various thicknesses. The subsurface sediment harbours a thick aquifer buried in 20.0 m from the surface of the earth and it is exposed to earth surface at VES 13 and 14. The resistivity range for the aquifer layer is between 1, 050 - 9, 300 Ωm and thickness is above 80.0 m.